UNFAIR BUSINESS PRACTICES TOWARDS CONSUMERS IN THE DIGITAL ERA: BETWEEN REGULATION AND REALITY - Imelda Mardayanti (PT. Radja Intercontinental Publishing, 2025)
The digital era has radically transformed the business landscape, creating an ecosystem that offers unprecedented transactional convenience alongside structural vulnerabilities for consumers. This journal critically analyzes the discrepancy between existing regulatory frameworks and the rapidly evolving reality of unfair business practices in Indonesia's digital space. Employing normative legal research methods and a critical approach, this study conducts horizontal and in-depth examinations of various forms of exploitative practices, including dark patterns, algorithmic bias, personalized dynamic pricing, review manipulation, and systematic violations of personal data. The research findings reveal that despite Indonesia's legal foundations such as Law Number 8 of 1999 concerning Consumer Protection, Law Number 19 of 2016 concerning Electronic Information and Transactions, and Law Number 27 of 2022 concerning Personal Data Protection, significant implementation gaps persist. Structural barriers include the pace of technological innovation outpacing legislative responses, information and technological asymmetry between businesses and regulators, technical difficulties in gathering evidence, low consumer digital literacy, and fragmentation among law enforcement institutions. This journal concludes that a more adaptive and proactive digital consumer protection paradigm is necessary. The proposed policy recommendations include: (1) more responsive and specific regulatory reform through the issuance of implementing technical regulations; (2) strengthening institutional capacity and inter-authority synergy through establishing integrated task forces; (3) consumer empowerment through digital literacy education and developing online dispute resolution (ODR) mechanisms; and (4) encouraging self-regulation and ethics by design principles among businesses. These findings contribute to the academic discourse on consumer law in the digital age and provide policymakers with a roadmap to bridge the gap between regulation and reality.